Optimization of Photothermal Catalytic Reaction of Ethyl Acetate and NO Catalyzed by Biochar-Supported MnOx-TiO2 Catalysts - Hongqiang Wang; Huan Zhang; Luye Wang; Shengpeng Mo; Xiaobin Zhou; Yinian Zhu; Zongqiang Zhu; Yinming Fan (Toxics, 2024)
The substitution of ethyl acetate for ammonia in NH3-SCR provides a novel strategy for the simultaneous removal of VOCs and NO. In this study, three distinct types of biochar were fabricated through pyrolysis at 700 °C. MnOx and TiO2 were sequentially loaded onto these biochar substrates via a hydrothermal process, yielding a family of biochar-based catalysts with optimized dosages. Upon exposure to xenon lamp irradiation at 240 °C, the biochar catalyst designated as 700-12-3GN, derived from Ginkgo shells, demonstrated the highest catalytic activity when contrasted with its counterparts prepared from moso bamboo and loofah. The conversion efficiencies for NO and ethyl acetate (EA) peaked at 73.66% and 62.09%, respectively, at a catalyst loading of 300 mg. The characterization results indicate that the 700-12-3GN catalyst exhibits superior activity, which can be attributed to the higher concentration of Mn4+ and Ti4+ species, along with its superior redox properties and suitable elemental distribution. Notably, the 700-12-3GN catalyst has the smallest specific surface area but the largest pore volume and average BJH pore size, indicating that the specific surface area is not the predominant factor affecting catalyst performance. Instead, pore volume and average BJH pore diameter appear to be the more influential parameters. This research provides a reference and prospect for the resource utilization of biochar and the development of photothermal co-catalytic ethyl acetate and NO at low cost.